Immunotherapy in cancer: Where we are and what the future brings? - Antea, Krsek; Kristina, Krpina; Miroslav, Samarzija; Dijana, Detel; Lara, Baticic; Vlatka, Sotosek (Trends in Immunotherapy, 2023)
Chemotherapy, radiotherapy, and surgery are recognized as the main treatment modalities for cancer. These therapeutic strategies may be effective in the early stages of the disease but are usually ineffective in advanced stages or when the cancer recurs. Recently, great efforts have been made to understand the complex interaction between the immune system and its surveillance of cancer and to find effective immunotherapies for all stages of cancer. Several types of immunotherapies, including adoptive immunotherapy, cancer vaccines, and immune checkpoint blockades, are receiving considerable attention. The clinical relevance of T lymphocytes and NK cells in combating carcinomas is beyond doubt, but their mechanism of tumor surveillance is far from being fully understood. In this review, much attention has been paid to the complex interplay between T lymphocytes, NK cells, and cancer cells and their role in immunotherapy. Moreover, in this review, we summarized the current data on cancer immunotherapies, especially cancer vaccines, T- and NK cell-based immunotherapies. In addition, we highlighted the role of biomarkers as important indicators of response to immunotherapy, as well as potential problems and solutions related to immunotherapy. Insights into the future of immunotherapy are also presented in this review.